2020
DOI: 10.1051/0004-6361/202038295
|View full text |Cite
|
Sign up to set email alerts
|

CARMENES input catalogue of M dwarfs

Abstract: Context. The relevance of M dwarfs in the search for potentially habitable Earth-sized planets has grown significantly in the last years. Aims. In our on-going effort to comprehensively and accurately characterise confirmed and potential planet-hosting M dwarfs, in particular for the CARMENES survey, we have carried out a comprehensive multi-band photometric analysis involving spectral energy distributions, luminosities, absolute magnitudes, colours, and spectral types, from which we have derived basic astroph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
134
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 134 publications
(150 citation statements)
references
References 202 publications
(216 reference statements)
15
134
0
1
Order By: Relevance
“…More than half of the M dwarfs (57.0 ± 7.3%) have spectral types M3.0 V to M5.0 V. This proportion remains stable when including the estimated spectral types of the unresolved secondary components (57.4 ± 6.9%). Translating these numbers into an observed mass function requires some care, but it seems to indicate that the number of stars increases up to about 0.3 M (∼ M4.0 V; Cifuentes et al 2020) and decreases for later M spectral subtypes. This maximum of the mass function, similar to other slope changes observed in very young open clusters (e.g.…”
Section: Statisticsmentioning
confidence: 99%
“…More than half of the M dwarfs (57.0 ± 7.3%) have spectral types M3.0 V to M5.0 V. This proportion remains stable when including the estimated spectral types of the unresolved secondary components (57.4 ± 6.9%). Translating these numbers into an observed mass function requires some care, but it seems to indicate that the number of stars increases up to about 0.3 M (∼ M4.0 V; Cifuentes et al 2020) and decreases for later M spectral subtypes. This maximum of the mass function, similar to other slope changes observed in very young open clusters (e.g.…”
Section: Statisticsmentioning
confidence: 99%
“…2.1, we extracted flux predictions in four filter bands (Johnson B and V and Gaia G BP , G RP ) from the theoretical spectra. Since the magnitudes in these bands have been measured for the majority of the CARMENES GTO sample (Cifuentes et al 2020), we were then able to compare the measured colors G BP − G RP and B − V to the theoretical predictions, as displayed in Fig. 7.…”
Section: Severalmentioning
confidence: 99%
“…Our final adopted stellar parameters and associated uncertainties are listed in Table 1. Cifuentes et al (2020) derived stellar parameters for Gl 414A and found that T eff =4100 K, R å =0.7016±0.0177 R e , L å =1.2530±0.0016 L e , and M å =0.7136±0.0234 M e . All of these values are in agreement with ours, to within 1σ.…”
Section: Minesweepermentioning
confidence: 99%